Implementasi Prinsip Keteladanan Berdasarkan 1 Timotius 4:12 : Studi Tentang Peran Kakak Tingkat terhadap Pembentukan Kehidupan Rohani Adik Tingkat dalam Lingkungan Asrama - Marlina Goga Djami; Merdiati Marbun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study, entitled “Implementation of the Principle of Exemplary Conduct Based on 1 Timothy 4:12: A Study on the Role of Senior Students in Shaping the Spiritual Life of Junior Students in a Dormitory Environment,” aims to examine the implementation of the biblical principle of exemplary conduct based on 1 Timothy 4:12 and to analyze the role of senior students in fostering the spiritual life of junior students within a dormitory setting. The dormitory environment provides intensive daily interactions that enable senior students to become role models influencing the attitudes, character, and spiritual growth of junior students. This study employs a qualitative approach using literature review and theological analysis to explore the relevance of biblical teachings to dormitory life. The findings reveal that the example demonstrated by senior students through their speech, behavior, faith, love, and holiness significantly contributes to the formation of junior students’ Christian character and spiritual maturity. In addition, positive interactions between senior and junior students encourage discipline, mutual respect, responsibility, and the development of a supportive spiritual community. The implementation of the principle of exemplary conduct based on 1 Timothy 4:12 is therefore essential in creating a dormitory environment that nurtures faith, moral integrity, and Christian values. This study concludes that exemplary leadership among senior students serves as an effective strategy for strengthening spiritual formation and character development, while providing practical recommendations for dormitory administrators to cultivate a faith-centered educational environment.